(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to describe the prevalence of medication adherence among outpatients with chronic obstructive pulmonary disease (COPD) at Nghe An Lung Hospital in 2024. Methods: A cross-sectional study was conducted on 399 outpatients with COPD at Nghe An Lung Hospital in 2024. Medication adherence among study participants was assessed using the Morisky-8 Scale (MMAS-8). Results: Among 399 study participants, the rate of high and low adherence was 55.0% and 12.0%, respectively. The proportion of female participants who sometimes stopped taking the medicine when feeling the symptoms were under control was higher than that of males. There was a significant difference with p-value<0.05. However, the results did not show a statistically significant difference in medication adherence among age groups and sex. Conclusion: The rate of study participants with high medication adherence was 55.0%. However, 49.2% of patients reported forgetting to take medicines. Therefore, family members need to help patients remember to take their medicines.